Strategi UMKM Desa Sungai Luar untuk Meningkatkan Perekonomian Pasca Pandemi Covid 19 - Siti Wardah; Rini Julianti; Rio Febrianto; Izhar Alan Ibrahim; Wahyu Wiranda (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The Covid-19 pandemic has had a profound impact on all people on Earth. The development of Covid-19 has not shown a significant decrease, and the public is urged to always be cautious in their activities, both at home and outside. The purpose of this community service is to provide efforts to develop UMKM strategies through sports and policies. The method used is through interviews and direct discussions with UMKM communities. The result of this community service is that almost all of the people in the Sungai Luar village, especially UMKM players, maintain good habits by living clean and healthy lives to optimize their health. In the UMKM group of Sungai Luar village, Batang Tuaka district, this community service activity is carried out as an effort of attention, concern, and health support to contribute to the community's economic growth. The activities carried out are to popularize sports and government policies as a support system for the community, especially UMKM players. The essence of the effort to popularize sports during the pandemic is to create social change for physical activity in the community during the recovery from Covid-19. Through socialization and education to popularize, and providing support for facility improvements, residents can better understand the concept of popularizing sports and government policies as a supporting system for the health of UMKM players in the Sungai Luar village in entrepreneurship, with the hope of helping to restore the economic cycle in the village.